2015
DOI: 10.15625/0866-7160/v36n4.6180
|View full text |Cite
|
Sign up to set email alerts
|

Expression of flagellin FLjB derived from Salmonella enterica serovar typhimurium in Escherichia coli BL21

Abstract: Flagellin FljB composes flagellar antigen (H:1,2) of S. Typhimurium. This kind of antigen increases immunogenicity of any conjugated antigen upon administration. Thus, it is supposed to have an enormous potentiality for vaccine development against bacterial infections and cancer diseases. fljB gene (1515 nucleotides) coding for mature FljB was amplified by PCR from genomic DNA of S. Typhimurium and inserted into pET32a(+) for expression in E. coli BL21. The protein FljB was well expressed under the fusion form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…For example Huyen et al . () found that IPTG concentrations were inversely related to flagellin productivity using pET32a.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For example Huyen et al . () found that IPTG concentrations were inversely related to flagellin productivity using pET32a.…”
Section: Resultsmentioning
confidence: 98%
“…Note that different IPTG concentrations were required for different pET vectors for soluble protein expression because of the metabolic burden release of recombinant E. coli (Lecina et al 2013). For example Huyen et al (2015) found that IPTG concentrations were inversely related to flagellin productivity using pET32a.…”
Section: Effects Of Iptg Concentration On Pyruvate Oxidase Expressionmentioning
confidence: 99%
“…In contrast, solubilization and refolding of protein from inclusion bodies is a common strategy although it requires denaturing conditions and a subsequent renaturing step, usually resulting in poor soluble protein recoveries [ 32 , 33 ]. Different approaches have been developed to prevent the accumulation of inclusion bodies in E. coli , such as the optimization of culture conditions, co-expression with molecular chaperones [ 34 , 35 ], lower growth temperature during gene induction [ 35 , 36 ], induction expression in early-log phase culture [ 37 ], and induction with lower levels of inducer concentration, such as Isopropyl β-D-1-thiogalactopyranoside (IPTG) [ 38 ]. In addition, several fusion tags have been developed to increase the solubility of overexpressed proteins, although with variable degrees of success.…”
Section: Resultsmentioning
confidence: 99%